ADCP Observations of Currents and Suspended Sediment in the Macrotidal Gulf of Martaban, Myanmar - Harris, Courtney K.; Wacht, Jacob T.; Fair, Matthew J.; Côté, Jessica M. (Frontiers in Earth Science, 2022)
The Ayeyarwady and Thanlwin Rivers, which drain Myanmar, together form one of the largest point sources of freshwater and sediment to the global ocean. Combined, these rivers annually deliver an estimated 485 Mt of sediment to the northern Andaman Sea. This sediment contributes to a perennially muddy zone within the macro-tidal Gulf of Martaban, but little is known about the processes that dominate dispersal and trapping of sediment there, as very few water column observations are available. A research cruise in December 2017 provided a rare opportunity to obtain Acoustic Doppler Current Profiler (ADCP) data along transects from the Gulf of Martaban and adjacent continental shelf. Two transects were obtained from the outer portion of the Gulf of Martaban in water depths that ranged from about 20 - 35 m. These showed very fast currents, especially during flood tide conditions, exceeding 1.5 m/s. The backscatter record from the ADCP indicated asymmetries in distribution of suspended sediment during the ebb versus flood phase of the tide. During ebb tidal conditions, the backscatter record indicated that sediment was transported in either a surface advected layer, or fairly well-mixed throughout the water column. In contrast, during flood tidal conditions, sediment was confined to the bottom boundary layer, even though the velocities were faster during flood than the ebb conditions. The vertical structure of the currents during flood tide conditions indicated the presence of sediment – induced stratification because currents within the near-bed turbid layers were relatively slow, but speeds increased markedly above these layers. This albeit limited dataset provides an exciting glimpse into the dynamics of sediment transport within the muddy, macrotidal Gulf of Martaban, and implies the importance of tidal straining and bottom nepheloid layer formation there.